THE ROLE OF NURSING MANAGEMENT IN OPTIMIZING THE ENVIRONMENT TO PREVENT INSOMNIA RISK IN THE ELDERLY AT THE SOCIAL SERVICE DEPARTMENT - Amaliyah, Eli; Hayati, Dewi (Journal Healthcare Education, 2025)
Insomnia is a prevalent health problem among the elderly worldwide, significantly impacting their quality of life and overall health. Environmental factors—such as room temperature, noise, lighting, and cleanliness—play a critical role in increasing insomnia risk. Nursing management is essential in optimizing these environmental conditions to support better sleep quality in elderly patients. Objective: This study aims to examine the role of nursing management in improving environmental factors to reduce insomnia risk among the elderly. Methods: A cross-sectional quantitative study was conducted with 45 elderly respondents selected by total sampling. Data collection used validated questionnaires including the Insomnia Rating Scale and environmental comfort assessments via Likert scales. Analysis involved univariate, bivariate (Fisher’s exact test), and multivariate logistic regression techniques. Results: Findings revealed that 66.7% of participants were at high risk of insomnia. Room temperature regulation was the most influential factor (RR = 5.10; p = 0.005), followed by noise control (RR = 3.85; p = 0.02), lighting (RR = 3.60; p = 0.03), and environmental cleanliness (RR = 3.40; p = 0.04). Poor environmental conditions significantly increased insomnia risk. Conclusion: Nursing management focusing on regulating room temperature, reducing noise, optimizing lighting, and maintaining cleanliness is crucial to decrease insomnia risk in the elderly. This study highlights the need for nursing education and policies emphasizing environmental management to enhance elderly sleep quality and well-being.